On a Search for Hidden Photon CDM by a Multicathode Counter - A. V. Kopylov; I. V. Orekhov; V. V. Petukhov (Advances in High Energy Physics)
We report a new technique of a multicathode counter (MCC) developed to search for hidden photon (HP) cold dark matter (CDM) with a mass from 5 to 500 eV. The method is suggested in the assumption that HP-photon mixing causes emission of single electrons from a metal cathode if the mass of hidden photon mγ′ is greater than a work function of the metal φW. The measured effect from HP should be dependent on φW and on the structure of electronic shells of the metal used as a cathode. Potentially this can be used for a verification of the results obtained. Some preliminary results for the upper limit for mixing parameter χ have been obtained for HP with a mass from 5 eV to 10 keV as a pure illustration of the potential of this technique. The efforts are continued to refine the procedure of data treatment and to improve the work of MCC. A new detector with a more developed design is under construction.